Business Development Strategy of Putri Mas Awal in Tegal Sari Mandala III Medan Denai District - Shintia Putri Aisyah; Annaisaburi Annaisaburi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Putri Mas business is a restaurant named "Putri Mas," operating from 5:00 PM to 4:30 AM WIB (Western Indonesian Time), located in Medan City. The initial establishment of Putri Mas restaurant encountered challenges during its inception as it was relatively unknown and adapting to the surrounding environment while maintaining the distinctiveness of its food offerings. The purpose of this research is to analyze the early development of Putri Mas restaurant, assess its internal and external environment, and identify the strategies that have enabled the business to thrive and endure for 18 years. This study aims to uncover the journey of Putri Mas restaurant from its humble beginnings to gaining a substantial number of patrons. The research methodology employed in this study is qualitative descriptive, utilizing interview as the data collection technique. The research is conducted to share the business development strategies that have contributed to the sustained success of Putri Mas restaurant over time.